PLAYING SHADOW PUPPET TO BUILD CHARACTER AND SPEAKING SKILL STUDENT FROM HOME - Astrid Wangsagirindra Pudjastawa (Jurusan Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2022)
One of the challenges of teaching Javanese is to make students speak communicatively to meet their needs while at the same time forming a good character in themselves. Role Playing-Based Language Teaching is a practical language teaching to improve speaking skills and at the same time instil certain positive feelings because they are given the opportunity to practice the language through their assignments and at the same time have to explore the characters presented. This classroom action research integrates role-playing in a shadow puppet game for SMK students in Malang. In this cycle, the students showed their active participation in producing the shadow puppet show from home. Another result found significant differences in the insight into the character values of groups of students who were taught using the role-playing learning model with conventional learning. These results reflect students' acceptance of the applied learning model because they feel that the given task helps them improve their speaking skills and positively affects their insight into character values.